Effects of early enteral glutamine supplementation on the outcome of severe burns: A randomized control study - Savita Arora; Chandni Shankar (Wolters Kluwer Medknow Publications, 2020)
Context: Burns is a condition associated with high mortality and morbidity. Nutrition plays an important role in the recovery of these patients. Amino acid glutamine is an important energy substrate for immune cells and for the intestinal epithelium. Glutamine is the preferred respiratory fuel for both lymphocytes and enterocytes. It stimulates the immune system and prevents catabolism. Aim: This study is aimed at determining if oral supplementation of glutamine can improve the outcome in patients with severe burns. Materials and Methods: It is a randomized controlled study. Patients of severe burns (30%-50%) were randomized into two groups. The first group was started on enteral nutrition but without glutamine supplementation. The second group received enteral nutrition with glutamine supplementation. All patients were followed up for a period of 1 month from the day of burns. Blood culture, wound culture, blood counts, and serum total proteins were done once every week for all patients. Statistical Analysis: Student's t-test was used to analyze the quantitative and Chi-square test was used to measure the qualitative data. Results: One hundred and two patients were included in the study, of which 49 were in Group 1 and 53 patients in Group 2. The mean percentage of burns in the two groups was comparable at 40.71% and 41.72%, respectively. Total leukocyte counts, mean duration of hospital stay, and mortality rates did not show any statistically significant difference between the two groups. However, serum protein levels showed a significant increase in the glutamine-supplemented group from the 3rd week onward. Wound infection rates were also lower in the glutamine-supplemented group, i.e., 19.5% vs. 2.1% by the 4th week. Conclusion: Glutamine supplementation has shown to enhance serum protein levels and hence improve nutritional status of these patients. It is also useful for its immunomodulatory effects, thus reducing burn wound infection, as shown by lesser number of burn wound culture positivity rates.